2009
DOI: 10.1021/ja907577p
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro Derivatives of Retinal Illuminate the Decisive Role of the C12-H Element in Photoisomerization and Rhodopsin Activation

Abstract: Rhodopsin, the visual pigment of the vertebrate rod cell, is among the best investigated members of the G-protein-coupled receptor family. Within this family a unique characteristic of visual pigments is their covalently bound chromophore, 11-cis retinal, which acts as an inverse agonist. Upon illumination it can be transformed into the all-trans isomer that acts as a full agonist. This photoisomerization process is extremely efficient: 2 out of 3 photons are effective, full stereoselectivity is achieved, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 93 publications
0
35
1
Order By: Relevance
“…Detecting this interaction suggests that it is in fact specific, and that it would likely be much stronger in solution. Moreover, such a small hydrophobic ligand would be unlikely to detect at all if not buried inside the molecule 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Detecting this interaction suggests that it is in fact specific, and that it would likely be much stronger in solution. Moreover, such a small hydrophobic ligand would be unlikely to detect at all if not buried inside the molecule 30 .…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Therefore, it comes as no surprise that much effort has been devoted to experimental [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and theoretical [31][32][33][34][35] investigations of synthetic pigments. However, there is a tight coupling between the chromophore and the receptor to achieve optimum stability of inactive dark and active conformations of the visual photopigment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] It has been reported that pyridyl-substituted cyclobutane coordinated with metallic ions can undergo isomerization/cleavage reactions upon thermalt reatment, [8][9][10][11] and recently,m etal-organic organopolymeric hybrid frameworks have been produced by using [2+ +2] cycloaddition reactions. [17][18][19] Moreover,R aman spectroscopyi su ltrasensitive to bond vibration, [19][20][21] as opposed to in situ X-ray diffraction, which is only sensitivet oc rystalline structure, so Ramans pectroscopy can even be applied to amorphousm aterials during the reactionp rocess. [14,15] Typically,e xsitu techniques such as nuclear magnetic resonance (NMR) spectroscopy and mass spectrometrya re used to study the yield of the cyclobutane cleavage reactions, which fail to monitor the whole reaction process.…”
mentioning
confidence: 99%
“…[12,13] Besidesc onventional heat resources, laser irradiation can also be applied to induce cleavage reaction. [17][18][19] Moreover,R aman spectroscopyi su ltrasensitive to bond vibration, [19][20][21] as opposed to in situ X-ray diffraction, which is only sensitivet oc rystalline structure, so Ramans pectroscopy can even be applied to amorphousm aterials during the reactionp rocess. [9,16] In situ time-resolved Raman spectroscopy is an advancedt echnique that can monitor the reaction processes and structure changes of molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation